Should Investor invest in both future and spot market? : An Analysis through Optimal Hedge Ratio - Jose, Babu; Lazar, D. (Asian Business Review, 2012)
This study is to estimate optimal hedge ratio with the variables from Indian futures and spot market and also nineteen individual stock prices. Diagonal VEC-GARCH model is used for the period from June 2000 to June 2011. The Empirical results confirm that there is effective risk sharing and hedging processes in Indian futures market. It is also found that Indian futures and spot markets have strong causal relationship; which allows the trader to make perfect arbitrage process and hedge their risks.
Keywords: Hedge Ratio; Futures Market; Spot Market; Causal Relationship